URGENSI PEMBELAJARAN BAHASA ARAB DALAM PENDIDIKAN ISLAM - Fahrurrozi.Z Fahrurrozi.Z (Reflektika, 2019)
Language has an important role in everyday life. Through language, humans can convey the intent and purpose that will be expressed to the interlocutor. Language is also very influential in the development of education in the world, this is because language and education are both dynamic or develop over time. One of the most famous languages is also included in the most widely used language by humans, namely Arabic. This research uses a literature study with a descriptive approach, namely the author wants to describe cases or phenomena that really occur and cases that are proven and true in the field. The results of this study indicate that the existence of Arabic can be characterized by the number of countries or nations that make Arabic a national language in their country, plus Arabic is also included as an international language. Not only that, the existence of Arabic is also marked as the language of the holy book of Islam which is also one of the most adherent religions in the world, therefore Arabic also has an important role in the world of Islamic education.